A steady-state performance analysis of a non-circular cylindrical floating ring journal bearing. (January 2017) - Soni, Sandeep; Vakharia, DP
This paper analyses the steady-state performance behaviour of a new type of journal bearing, i.e. the non-circular cylindrical floating ring journal bearing. It consists of a floating ring in between the shaft and the upper and lower lobes of a two-lobe bearing. The journal and the inner surface of the ring are cylindrical while bearing surfaces are non-circular. The classical Navier–Stokes equations in the modified form together with the continuity equation are being solved by the finite element method. The cylindrical coordinates form of the Navier–Stokes equation and continuity equation are used in the present analysis to compute the important proposed bearing characteristics. In this analytical study, the finite bearing approximation ( L / D =1) with a C 2 / C 1 value of 0.70 and 1.30 are being used to simulate the behaviour of non-circular cylindrical floating ring journal bearing. The Reynold's boundary condition is used to enumerate the performance of the proposed bearing. In the present analysis, the steady-state parameters in terms of an inner and outer film eccentricity ratio, a speed ratio, attitude angle, load capacity, friction coefficient parameter, axial oil flow and rise in temperature variable are determined. The results reveal that the steady-state performance of the non-circular floating ring journal bearing is superior to a plain cylindrical floating ring journal bearing.